ROS-Activated homodimeric podophyllotoxin nanomedicine with self-accelerating drug release for efficient cancer eradication - Bingfeng Liang; Dangxia Zhou (Taylor & Francis Group, 2021)
Although podophyllotoxin (POD) demonstrates high efficiency to inhibit various cancers, its clinic application is limited to poor bioavailability. Nanoparticles derived from homodimeric prodrugs with high drug loading potential are emerging as promising nanomedicines. However, complete intracellular drug release remains a major hindrance to the use of homodimeric prodrugs-based nanomedicine. We sought to develop a reactive oxygen species (ROS) responsive POD dimeric prodrug by incorporating vitamin K3 (VK3) and Pluronic F127 to synthesize a spheroid nanoparticle (PTV-NPs). PTV-NPs with high POD content could release drugs under the ROS enrichment microenvironment in cancer cells. The released VK3 could produce abundant ROS selectively in tumor cells catalyzed by the overexpressed NAD(P)H: quinone oxidoreductase-1 (NQO1) enzyme. In turn, the resultant high ROS concentration promoted the conversion of POD dimeric prodrug to POD monomer, thereby achieving the selective killing of cancer cells with weak system toxicity. In vitro and in vivo studies consistently confirmed that PTV-NPs exhibit high drug loading potential and upstanding bioavailability. They are also effectively internalized by tumor cells, induce abundant intracellular ROS generation, and have high tumor-specific cytotoxicity. This ROS-responsive dimeric prodrug nanoplatform characterized by selective self-amplification drug release may hold promise in the field of antitumor drug delivery.